ANALISIS DAMPAK PANJANG WAKTU SEKOLAH TERHADAP PEMBENTUKAN NILAI-NILAI PENDIDIKAN ISLAM DI TADIKA AL-FIKH ORCHARD, MALAYSIA - Dian Wijaya Kusuma; Muhammad Qorib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the effect of extended school duration on the formation of Islamic educational values at the Tadika level in Al-Fikh Orchard School, Malaysia. A descriptive qualitative approach was applied through observation, semi-structured interviews, and documentation involving the principal, teachers, and parents. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that full-day schooling supports the internalization of aqidah, worship, moral conduct, and social values through consistent habituation embedded in daily activities. Teacher role modeling and a religious school culture strengthen the process. Properly managed school duration contributes to effective Islamic character formation among participants.